PERLINDUNGAN TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA OLEH ANGGOTA KEPOLISIAN (Studi Kasus Nomor: 50/PID/2022/PT.TJK) - Ubayidillah, Moch. Rafli; Borman, Syahrul; Aribawa, Muhammad Yustino; Cornelis, Vieta Imelda (Gapenas Publisher, 2025)
Drug abuse in Indonesia is a serious problem that not only affects public health but also threatens the legitimacy of law enforcement institutions. Cases involving members of the Indonesian National Police (Polri) who have been caught using narcotics are ironic because the very officials who are supposed to be at the forefront of eradication efforts have instead become perpetrators. The urgency of this study lies in the lack of research highlighting the integration of criminal and administrative accountability for Polri officials who commit narcotics crimes. The main questions asked are what forms of criminal and administrative accountability are imposed on members of the Indonesian National Police in cases of drug abuse, and to what extent are legal norms implemented consistently. This study uses a normative legal research design with a qualitative approach. Data was obtained through a literature study by examining primary legal materials in the form of laws and court decisions, as well as secondary legal materials in the form of literature and scientific journals. The analysis was conducted normatively and qualitatively using a legislative and case approach, supported by Satjipto Rahardjo's progressive legal theory and white collar crime theory. The results of the study show a discrepancy between legal norms and practice. The verdict against Tito Satria Perdana bin Supraptono only imposed criminal sanctions, without clarity on the administrative sanctions that should have been applied based on Government Regulation No. 2 of 2003. These findings reveal weak internal supervision within the Indonesian National Police, potential impunity, and declining public trust. In conclusion, narcotics abuse by Polri officers cannot be viewed solely as an individual violation, but rather as an institutional symptom that requires regulatory reform, strengthened supervision, and transparency. Further research is recommended to explore the role of external supervisory institutions in ensuring the accountability of law enforcement officials.